Penerapan Data Mining dengan Metode K-Means untuk Menentukan Penilaian Kinerja Pengasuh Anak pada Panti Asuhan Eben Heazer - Pinta, Elysa; Rika Rosnelly (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
An orphanage is a social institution whose job is to provide care and guidance for children who do not have parents or come from poor families. Caregivers play a crucial role in fostering children's independence across emotional, behavioral, and moral dimensions. At Eben Heazer Orphanage, caregivers function as educators, mentors, and motivators. As educators, they instill ethical values and religious devotion; as mentors, they assist in discovering children's interests and talents; and as motivators, they encourage self-reliance. Nevertheless, the caregivers' contribution to developing children's independence remains suboptimal. Therefore, an evaluation of caregiver performance is essential to continually enhance services for the children. This evaluation not only enables management to assess the extent to which caregivers fulfill their duties but also provides a foundation for further training and development programs. In this way, the quality of care can be progressively improved to meet the children's needs. Furthermore, the application of technologies such as the K-Means algorithm supports transparency and objectivity in the assessment process, ensuring that each caregiver receives a fair evaluation based on actual performance. This initiative is expected to establish a more professional and measurable caregiving system at Eben Heazer Orphanage.